Kualitas Hidup Pasien dengan Talasemia - Intan Angnechintia Buka; Titi Pambudi Karuniawati (LPPM STIKES Mataram, 2024)
Abstract Introduction: Thalassemia is a genetic disorder whose incidence is increasing, this can be seen in the 2012-2018 data which shows an increase from 4,896 cases to 9,028 cases. Thalassemia patient especially transfusion dependent thalassemia (TDT), need a routine transfusion to support their lives. The severity of the disease and the therapy undertaken by patients can affect their quality of life. Objective: To review the disease development of thalassemia and its treatment, as well as factors that affecting the quality of life of thalassemia. Method: This literature review examines thalassemia and its impact on quality of life, using literature source in the form of book and national and international journal which published in the last ten years. The literature research using search engines such as Google Scholar, PubMed, and NCBI. Result: Previous study shown that thalassemia and its long-term therapy could affect patient’s quality of life. There are some factors that could affect quality of life such as serum ferritin levels, iron chelation therapy, pre-transfusion hemoglobin, and transfusion frequency. Conclusion: The reduced or absence production of alpha or beta globin causes chronic anemia in thalassemia patients, requiring regular transfusion to support their lives. Long-term therapy carried out by thalassemia patients as a whole, affect the patient’s quality of life, especially in school function. Factors that could affect the patient’s quality of life are serum ferritin levels, iron chelation, pre-transfusion hemoglobin, and transfusion frequency.